Influence of fixation systems on complications after tibial plateau leveling osteotomy in dogs greater than 45.4 kilograms (100 lb). Issue 4 (6th January 2019) - Chiu, King Wa; Amsellem, Pierre M.; Yu, Jenny; Ho, Pui Shan; Radasch, Robert
Abstract: Objective: To determine the influence of 3 fixation systems on complications rate after tibial plateau leveling osteotomy (TPLO) in dogs >45.4 kg. Study design: Retrospective case series. Sample population: Dogs (N = 287, 342 stifles) >45.4 kg with cranial cruciate ligament tear treated with TPLO. Methods: The medical records of dogs treated with TPLO were reviewed for fixation and postoperative complications, with a follow‐up of at least 6 weeks. A random effects logistic regression model was used to evaluate the association between the type of TPLO fixation system and complications. Results: The fixation systems included a 3.5‐mm broad TPLO plate alone (8P; 78.4%), a 3.5‐mm broad TPLO plate with SOP (String of Pearls) plate (8AP; 14.9%), and a 3.5‐mm standard TPLO plate (6P; 6.7%). Among the included stifles, 214 (62.6%) fixation systems were classified as locking, and 128 (37.4%) were classified as nonlocking. The fixation system was predictive of complications. The 8P had the lowest odds ratio for complication among the 3 fixation systems. Odds of developing complications were higher with the 8AP fixation system than with the 8P fixation system. Locking fixation eliminated the association between weight and complication rate. Conclusion: Fixation of a TPLO with the 8AP increased the risk of complications compared with the 8P in this population of large dogs. Clinical significance: Locking fixation of TPLO with a 3.5‐mm broad TPLO plate alone should be considered in large dogs because it may reduce complications.